2009
DOI: 10.26850/1678-4618eqj.v34.1.2009.p19-24
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid extraction from Alpinia zerumbet (Pers.) Burtt et Smith leaves using different techniques and solvents

Abstract: The current study aims to verify the best method for a rapid and efficient extraction of flavonoids from Alpinia zerumbet. Dried leaves were extracted using distillated water and ethanol 70% by extraction methods of shaking maceration, ultrasonic, microwave and stirring. By the application of TLC and reversedphase HPLC techniques the rutin and kaempferol-3-O-glucuronide were detected. Ethanol 70% was more efficient for flavonoids extraction than water. No significant yielding variation was verified for ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…In our work; the aqueous fraction rich in phenols was more effective. This finding suggests that solvent extraction technique affects secondary metabolites extraction and bioactivity [30] .…”
Section: Discussion Of the Antibacterial Activitymentioning
confidence: 88%
“…In our work; the aqueous fraction rich in phenols was more effective. This finding suggests that solvent extraction technique affects secondary metabolites extraction and bioactivity [30] .…”
Section: Discussion Of the Antibacterial Activitymentioning
confidence: 88%
“…purpurata crude extracts inhibited C. neoformans, T. rubrum and M. canis fungi. Hydroalcoholic extracts and polar fractions, such as ethyl acetate and butanol, of A. zerumbet and A. purpurata contain high concentrations of phenolic compounds, such as flavonoids [20,21,28] , which present antimicrobial properties [29] . species was also verified by Habsah et al [30] , different from the findings reported by Mathew and Victório [5] cited above.…”
Section: Resultsmentioning
confidence: 99%
“…For antimicrobial activity, crude extracts were tested, along with hexane, dichloromethane, ethyl acetate and nbutanol fractions. As standard, the flavonoid rutin (Merck ® ) was used by its previously identification in extracts of A. zerumbet and A. purpurata [20,21] . The nonpolar samples were initially solubilized in DMSO (50 mg/ml) and diluted in sterile distilled water 1:3 (1 part of the sample in DMSO + 2 parts of sterile distilled water) before being dropped onto the surface of inoculated medium.…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa) Enterococ...mentioning
confidence: 99%
“…Burtt & R.M. Sm (Zingiberaceae), conhecida popularmente no Brasil como colônia, tem amplo emprego na medicina tradicional e popular como diurética e anti-hipertensiva (KRESS; PRINCE; WILLIAMS, 2002;MORITA et al, 1996;MPALANTINOS et al, 1998;VICTÓRIO et al, 2009). A espécie vem sendo utilizada em diversos programas de fitoterapia em saúde pública, cultivada em hortos medicinais e Arranjos Produtivos Locais de plantas medicinais e fitoterápicos apoiados pelo Ministério da Saúde.…”
Section: Introductionunclassified
“…Estudos farmacológicos associam as atividades anti-hipertensiva e diurética com a presença de compostos fenólicos, com destaque para os flavonoides (MPALANTINOS et al, 1998;KUSTER, 2009).…”
Section: Introductionunclassified